Disseleneto de p-metoxi fenila atenua o prejuízo cognitivo e a injúria cerebral em um modelo da doença de Alzheimer em roedores - Pinton, Simone (2012)
Alzheimer s disease (AD) is a progressive neurodegenerative disorder, mainly characterized by memory and intellectual capacity loss. AD is characterized by deposition of amyloid-β peptide, neurofibrillary tangles, neuroinflammation, energy metabolism impairment, oxidative stress and synaptic dysfunction and loss. Its multiple pathological pathways contribute to the difficulty of AD treatment and prevention. Thus, the development of new therapies for AD curing or treatment is a challenge. The purpose of this study was to indicate an organoselenium moiety, p,p -dimethoxyl-diphenyl diselenide [(MeOPhSe)2], as a promising alternative for the treatment and prevention of sporadic dementia of Alzheimer-type (SDAT), using an experimental model of dementia induced by intracerebroventricular (i.c.v.) injection of streptozotocin (STZ) in rodents. Initially, it was investigated the prophylactic action of (MeOPhSe)2. For this, mice were treated with (MeOPhSe)2 (25 mg/kg, by gavage) and STZ (2μl of 2,5mg/ml solution; i.c.v.) or vehicles, and 48h after that, the treatment was repeated. The tasks of step-down-type passive-avoidance (SDPA), Y-maze and Morris water-maze (MWM), that followed this treatment, showed that (MeOPhSe)2 protected against the impairment in learning and memory caused by i.c.v. injection of STZ in mice. (MeOPhSe)2 protected against the increase in reactive species (RS) and the reduction of glutathione (GSH) levels, as well as modulated the antioxidant enzymes. (MeOPhSe)2 inhibited the acetylcholinesterase (AChE) activity, which was increased by STZ. Subsequently, it was investigated the effectiveness of (MeOPhSe)2 in reversing the cognitive impairment and neuronal damage induced by STZ. Therefore, rats were injected with STZ (1.0 mg/8μl; 4μl/ventricle) twice, 48h apart. After 21 days of STZ injection, regular diet fed rats were supplemented with 10ppm of (MeOPhSe)2 during 30 days. At the end of this period, it was observed that (MeOPhSe)2 dietary supplementation reversed STZ-induced memory impairment in MWM, SDPA and object recognition tasks. The results on SDPA and object recognition tasks demonstrated that the (MeOPhSe)2 improved memory in rats per se. STZ enhanced the RS and protein nitration levels in cortex and decreased GSH levels on hippocampus of rats, (MeOPhSe)2 reversed these alterations. (MeOPhSe)2 normalized AChE activity (which was enhanced by STZ) in both cortex and hippocampus, but did not reverse the deficit in cerebral glucose metabolism (ATP turnover was decrease by STZ). (MeOPhSe)2 was effective in reducing STZ-induced neuronal (apoptosis) loss. Moreover, (MeOPhSe)2 suppressed neuroinflammation induced by STZ in the rats hippocampus. The organoselenium inhibited activation of microglia and astrogliosis. Based on these results, it was concluded that: 1) (MeOPhSe)2 protected and reversed the cognitive abilities decline; 2) the mechanisms involved in the neuroprotective effect of (MeOPhSe)2 are: antioxidant, AChE inhibitor; inflammation suppressor; 3) (MeOPhSe)2 did not alter the energy metabolism; and 4) (MeOPhSe)2 reduced the neuronal death. Therefore, the present study demonstrated that (MeOPhSe)2 is a promising alternative for the drug studies for treatment of cognitive disorders such as SDAT.